The Relationship between OCBI and Family Motivation through Self-Efficacy and Welfare in Makassar City Banking Offices - Rahmawati Andi (University of Merdeka Malang, 2021)
Employees often show a distinctive personality through their preference for family needs over jobs. Therefore, this study explores the relationship between family motivation and OCBI mediated by self-efficacy and well-being in the workplace. This research model varies from previous studies and provides the novelty of the study. As a research unit, this study uses a sample of bank employees in Makassar City with at least five years' experience as respondents. They are considered capable of delivering reliable data about the research issue (purposive sampling) using the WarpPLS 7.0 analysis tool. Interestingly, this study's new concept has revealed no evidence of an interaction between family motivation and OCBI. In this research model, all the relationships between variables were positive and significant. A recent finding of the relationship between self-efficacy and well-being in the workplace has been found and may lead to an understanding of the association between family motivation and OCBI. Empirical evidence of self-efficacy and well-being is a recent discovery that theoretically contributes to the relationship between family motivation and OCBI. In theory, this study also contributes to the existing pro-social motivation theory, explaining the impact of family motivation on OCBI in banking.DOI: https://doi.org/10.26905/jkdp.v25i1.5458